Analyzing Business Strategies Through the Business Model Canvas (BMC): A Case Study of BMT Huwaiza - Azzaida, Ibna R; Budiman, Surya (Indonesian Development of Economics and Administration Journal, 2025)
This study aims to analyze the business strategy of BMT Huwaiza–Depok using the Business Model Canvas (BMC) approach supported by ATLAS.ti 9 qualitative analysis software. Data were collected through in-depth interviews with four key informants: Mrs. Namah Purnama, A.Md. (Chairperson of the Board, BMT Huwaiza), Mrs. Ani Apriani, S.Pd. (Internal Auditor and Acting Manager, BMT Huwaiza), Ms. Dwilingga Hesya Ramadhanty, S.Ak. (Financial Administration, BMT Huwaiza), and Mrs. Dr. Endah Meiria, S.E., M.Si. (Academic). The results show that BMT Huwaiza’s business strategy is built on three main pillars: commitment to Sharia principles as its core identity, personalized and inclusive service, and digitalization as a tool for efficiency and accessibility. The ATLAS.ti coding process generated 367 coded segments across 9 major BMC categories, business strategy and social impact. The top three categories were Value Proposition (64 codes), Social Impact (44 codes), and Key Activities (43 codes), indicating the organization’s emphasis on creating value, delivering social impact, and executing core operations. In addition, partnership development, cost-efficiency strategies, and ethical human resource management play a supporting role in BMT Huwaiza’s success. These findings demonstrate that the BMC framework is effective in capturing the structure and ethical dimensions of a Sharia-based cooperative business model.